Faktor-Faktor Yang Mempengaruhi Produksi Kelapa Sawit (Elaeis guineensis Jacq) Di PT.Perkebunan Nusantara II Kebun Sawit Seberang Kabupaten Langkat - Imelda Putri Br Ginting; Muhammad Jamil; Supristiwendi Supristiwendi (Jurnal Penelitian Agrisamudra, 2022)
This study aims to analyze the factors that affect oil palm productionat at PT. Perkebunan Nusantara 2 oil palm plantations across the Sawit opposite Subdistrict, Langkat Regency .This research was carried out at PT Perkebunan Nusantara 2 oil palm plantations across the Sawit opposite Subdistrict, Langkat Regency. the data used is secondary data. The analysis used in this research is multiple linier regression analysis. The sample used is time series data for the last three years and the data is presented in the form of monthly data with a total of 108 data. The independent variables used in this study were the area of the land, the weight of the bunches, the number of bunches and the rainfall. while the dependent variable is oil palm production. The results of this study indicate that the variable area of land (X1) has no significant effect on oil palm production. The variable weight of bunches (X2) has a significant effect on oil palm production. variable number of bunches (X3) has a significant effect on oil palm production. variable rainfall (X4) has no significant effect on oil palm production at PT Perkebunan Nusantara 2 oil palm plantations across the Sawit opposite Subdistrict, Langkat Regency.